Spatial and temporal dynamics of the urban heat island effect in a small Brazilian city - Ribeiro, Maria Clara Aparecida; Pinton, Leandro de Godoi; Cardoso, Renata dos Santos [UNESP]; Amorim, Margarete Cristiane de Costa Trindade [UNESP] (Wiley, 2023)
This study examined the spatial and temporal patterns of the canopy layer urban heat islands (UHIUCL) in a small city in southeastern Brazil using the local climate zone (LCZ) system. We analysed the influence of weather conditions, LCZs characteristics, and local surface relief on the UHIUCL magnitudes. Mobile traverses were used to measure air temperatures during representative nights of wet and dry seasons. Daily maximum magnitudes were observed in compact classes (LCZs 3 and 7) under ideal weather conditions (dry, clear skies, and calm) and higher anthropogenic heat release (weekdays). Seasonal effects on LCZ thermal differences were negligible. The peripheral landscapes were warmer than the city centre in both seasons. Among the warmer areas in the city, magnitudes in compact LCZs 3 and 7 were consistently higher than in LCZ 6. In general, representative sites of the main ‘built’ LCZs in the study area exhibit similar inter-zone temperature patterns to those reported for cities of different sizes from tropical and midlatitude regions. Thermal contrasts of ΔTLCZ 3 − D in the study area reveal significant evidence that small cities can have as strong heat islands as bigger cities. These findings highlight the importance of the LCZ system to identify the main controlling factors driving such thermal differences and the need to extend the application of this approach in other South American cities to yield systematic data of UHIUCL for urban planning given the coming challenges of climate change over the region.
Keywords: canopy-layer air temperature; local climate zones; mobile traverses; South America; tropical urban climatology; urban heat islands